2016
DOI: 10.1016/j.reth.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-activated medium selectively eliminates undifferentiated human induced pluripotent stem cells

Abstract: Human pluripotent stem cells, including human induced pluripotent stem cells (hiPSCs), are promising materials for regenerative medicine and cell transplantation therapy. However, tumorigenic potential of residual undifferentiated stem cells hampers their use in these therapies. Therefore, it is important to develop methods that selectively eliminate undifferentiated stem cells from a population of differentiated cells before their transplantation. In the present study, we investigated whether plasma-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The scratch treated with 47 mJ nsDBD plasma (right) has greater gap closure and more migrating cells in the gap as compared to the untreated scratch (left) Fig. 64 Effect of PAM on the viability of undifferentiated hiPSCs and RA-induced differentiated hiPSCs (Matsumoto et al 2016). 201B7 hiPSCs were cultured in a medium containing 5 lM RA for 9 days.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
See 3 more Smart Citations
“…The scratch treated with 47 mJ nsDBD plasma (right) has greater gap closure and more migrating cells in the gap as compared to the untreated scratch (left) Fig. 64 Effect of PAM on the viability of undifferentiated hiPSCs and RA-induced differentiated hiPSCs (Matsumoto et al 2016). 201B7 hiPSCs were cultured in a medium containing 5 lM RA for 9 days.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…We found that hiPSCs are more sensitive to PAM than are NHDFs [see Fig. 63, (Matsumoto et al 2016)]. We also investigated differences in cell viability between undifferentiated hiPSCs and retinoic acid (RA)-induced differentiated hiPSCs following treatment with PAM and found that undifferentiated cells are more sensitive than are differentiated cells (see Fig.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have tried to understand the working mechanisms of PAM in its tumoricidal activity. Since PAM contains relatively long-lived reactive species compared to direct plasma treatment, hydrogen peroxide and nitric oxide ions were identified as the main players in PAM reactivity [7][8][9][10][11][12][13][14][15][16]. The actions of reactive oxygen species (ROS) and reactive nitrogen species (RNS) are distinguished in biological systems [17].…”
Section: Introductionmentioning
confidence: 99%